PERENCANAAN INDIVIDUAL BIMBINGAN DAN KONSELING KOMPREHENSIF KELAS VII SMPN 3 SUNGAI AMBAWANG KUBU RAYA - Deana, Miranda Putri; Yuline, Yuline; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractIndividual planning guidance and counseling is an assistance service to students. Which can be done individually or in groups to foster students' independence in the development of personal life, social life, learning skills and career planning. In the implementation of individual planning comprehensive guidance and counseling includes personal-social individual planning, individual learning planning and individual career planning. As well as the inhibiting factors in carrying out individual planning services and the efforts made in overcoming obstacles. Therefore, researchers want to know the implementation of individual planning comprehensive guidance and counseling. The research problem is "How to individual plan VII Class Students in Negeri 03 Sungai Ambawang". The purpose of this research is to find out about the implementation of individual planning comprehensive guidance and counseling in SMP Negeri 3 Sungai Ambawang. The method used is descriptive with a quantitative approach in the form of survey research. The research sample of 40 students and 1 teacher guidance and counseling. Data collection techniques used are indirect communication and direct communication in the form of questionnaires and interviews. Data analysis technique is percentage. Overall implementation of individual planning comprehensive guidance and counseling in SMP Negeri 3 Sungai ambawang obtained 63.13% category Good Enough. The implementation of individual private social planning obtained 63.19% good enough category. Implementation of individual learning planning obtained 63.39% good enough category .. implementation of individual career planning obtained 62.72% good enough category. Keywords: Comprehensive Counseling Guidance,Individual Planning